On the Performance of Overlaid Wireless Sensor Transmission With RF Energy Harvesting - Wu, Tianqing; Yang, Hong-Chuan (IEEE journal on selected areas in communications, 2015)
RF energy harvesting is a promising potential solution for providing convenient and perpetual energy supply to low-power wireless sensor networks. In this paper, we investigate the performance of overlaid wireless sensor transmission powered by RF energy harvesting from existing wireless system. Specifically, we derive the exact closed-form expression for the distribution function of harvested energy over a certain number of channel coherence time over Rayleigh fading channels with the consideration of hardware limitation, such as energy harvesting sensitivity and harvesting efficiency. We also obtain the exact distribution of the number of coherence time needed for fully charging the sensor. Based on these analytical results, we analyze the average packet delay and packet loss probability of sensor transmission subject to interference from existing system, for delay insensitive traffics and delay sensitive traffics, respectively. Finally, we investigate the optimal design of energy storage capacity of the sensor nodes to minimize the average packet transmission delay for delay insensitive traffics with two candidate transmission strategies.